TIPE KESALAHAN NEWMAN PADA HASIL PENGUKURAN - Nursupiamin Nursupiamin (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2020)
The command of learning in the Qur'an aims to enable people to gain knowledge, experience, and learning in living life, especially in overcoming the problems encountered. Mathematics is a branch of science that plays an important role in life whose application is seen in various disciplines. Measurement material is one of the subjects of Mathematics I taught in the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) semester V. The results of individual assignments show that the scores obtained are not optimal yet there are still many errors in completion. In this study, the authors used the Newman procedure error approach. Based on the results of the study, the percentage of reading errors reached 24.5%, understanding errors 17.6%, transformation errors 15.6%, processing skills errors 16.6% and answers writing errors 25.7%. The results of the interview show that reading errors are generally caused by incompetence in writing words/symbols due to factors that forget or do not know in standard writing. Misunderstanding is caused by students having difficulty understanding the phrase "standard unit writing", consequently also difficulty in determining the final result. Transformation errors are caused by errors in converting to standard units and errors for process skills are due to inaccuracy in writing answers so that they experience calculation errors that also have an impact on writing the final result. Finally, the answer writing error is caused by inaccuracy in writing the final answer caused by other types of mistakes made previously.